Performance of a Semi Adiabatic Diesel Engine Fuelled with Jatropha Bio-diesel - N. Janardhan; M. V. S. Murali Krishna (Technological Innovation in Engineering Research Vol. 4, 2022)
Background of the Problem: In the scenario of fast impoverish of conventional fuels, ever hike of pollution levels with conventional fuels, increase of financial bundle on emerging countries due to import of crude petroleum with foreign currency exchange rate, the investigation for alternative fuels has become relevant and important. Oils extracted from the seeds of the plant, and alcohols, manufactured from biomass are important replacements for conventional diesel, as they are reclaimable. Oils from the seeds of the plants have energy fuels per unit mass and cetane number (a measure of ignition quality in diesel engine) are on par with diesel fuel. But they have high viscidity and low fugitive. On the other hand, biofuels have high transient. But they have low cetane number and low energy content per unit mass. Hence oils from the seeds of the plants are chemically converted into biodiesel to reduce viscidity and raised ignition quality. The problems of biodiesel are solved with engine, semi adiabatic diesel engine, which mitigate the heat flow to the coolant. Aim: Trials were performed on a low heat rejection (LHR) diesel engine or semi adiabatic diesel engine employing an air gap insulated piston with 3-mm air gap, with stainless steel crown and air gap insulated liner with stainless steel insert with various functions of conditions of jatropha bio-diesel with varied injection timing and injector opening pressure. Study Design: Configuration of the engine, conventional engine (CE) or low heat rejection (LHR), test fuels diesel or jatropha biodiesel, varied injection timing, varied injection pressure. Objectives: 1. Preparation of biodiesel from crude vegetable oil, 2. Determination of optimum injection timing for a conventional engine (CE) and LHR engine with biodiesel, 3. Determination of performance parameters, pollution levels and combustion characteristics at recommended injection timing and optimum injection timing and various injector opening pressure with biodiesel. Methodology: Performance parameters were determined at various values of brake mean effective pressure. Pollution levels of smoke and oxides of nitrogen (NOx) were recorded at the full load operation of the engine. Combustion characteristics at full load operation were determined with TDC (top dead centre) encoder, pressure transducer, console and special pressure-crank angle software package. Brief Results: Conventional engine (CE) showed deteriorated performance, while LHR engine showed improved performance with bio-diesel operation at recommended injection timing and pressure. The performance of both version of the engine improved with advanced injection timing and higher injection pressure when compared with CE with pure diesel operation. Peak brake thermal efficiency increased by 4%, smoke levels decreased by 4% and NOx levels increased by 37% with biodiesel operation on LHR engine at its optimum injection timing, when compared with neat diesel operation on CE at manufacturer’s recommended injection timing.